Positional deprivation and support for radical right and radical left parties*. (24th December 2018) - Burgoon, Brian; van Noort, Sam; Rooduijn, Matthijs; Underhill, Geoffrey
SUMMARY: We explore how support for radical parties of both the left and right may be shaped by what we call 'positional deprivation', where growth in income of individuals at a given point in the income distribution is outpaced by income growth elsewhere in that distribution. We argue that positional deprivation captures the combination of over-time and relative misfortune that can be expected to distinctly spur support for radical left and right parties. We explore this possibility by matching new measures of positional deprivation to individual-level survey data on party preferences in 20 European countries from 2002 to 2014. We find that positional deprivation is robustly correlated with supporting radical populist parties. First, positional deprivation generally, measured as average income growth across deciles of a country's income distribution minus a respondent's own decile's growth, is associated with respondents' retreat from mainstream parties and with support for both radical right and, particularly, radical left parties. Second, positional deprivation relative to the highest and the lowest ends of the income spectrum play out differently for radical right and for radical left support. A respondent's positional deprivation relative to the wealthiest decile's growth in his or her country tends to spur support for radical left but not radical right parties. In contrast, positional deprivation relative to the poorest decile's growth in a respondent's country tends to spur support for radical right but not left parties. The results suggest that the combination of over-time and relative economic misfortune may be key to how economic experience shapes radical backlash of the left and right.